Pengaruh Kompetensi Intelektual, Etos dan Motivasi Berprestasi Terhadap Kinerja Karyawan CV. Bali Printing Center di Denpasar - Suadnyani, Ni Luh Putu Eka; Suartina, I Wayan; Sunny, Milla Permata (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Performance or achievement is part of the results that a person has achieved from his work behavior in carrying out work activities. Employee performance is influenced by many factors such as intellectual competence, work ethic and achievement motivation. The formulation of problems and objectives in this study how and to determine the influence of intellectual competence, work ethic and achievement motivation on employee performance. The location of this research is on CV. Bali Printing Center in Denpasar and the sample used was 47 respondents. The data analysis techniques used are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t Test and F Test. Based on the results of the study, it can be seen that intellectual competence has a significant positive effect on employee performance, work ethic has a significant positive effect on employee performance, achievement motivation has a significant positive effect on employee performance and simultaneously intellectual competence, work ethic and achievement motivation have a significant effect on employee performance. The magnitude of the influence of the independent variable on employee performance was 54.2%.